Las colecciones botánicas y sus plagas - Katinas, Liliana (1995)
Collections are the permanent records of our natural heritage and contain the materials that support the research of many scientific disciplines, including those working to preserve biodiversity and monitor global change. This is the basic reason why it is a permanent obligation to protect the collections from the attack of pests. The different types of pests that infest botanical collections and their control are discussed in this paper, with special emphasis in the Herbarium of Museo de La Plata (LP). Two types of control pests, rutinary and periodical, were established. The first one implies the continuous use of chemical substances like piretrines, vapones and mothballs, or physical actions with low and high temperatures. The periodical control includes the masive fumigation with deltametrines. In addition, the importance of a preserving behavior concerning to the users of botanical collections are emphasized.